X-chromosome inactivation and epigenetic fluidity in human embryonic stem cells - Silva, Susana S; Rowntree, Rebecca K; Mekhoubad, Shila; Lee, Jeannie T (Proceedings of the National Academy of Sciences - PNAS, 2008)
With the potential to give rise to all somatic cell types, human embryonic stem cells (hESC) have generated enormous interest as agents of cell replacement therapy. One potential limitation is their safety in vivo. Although several studies have focused on concerns over genomic stability ex vivo, few have analyzed epigenetic stability. Here, we use tools of the epigenetic phenomenon, X-chromosome inactivation (XCI), to investigate their epigenetic properties. Among 11 distinct hESC lines, we find a high degree of variability. We show that, like mouse ESC, hESC in principle have the capacity to recapitulate XCI when induced to differentiate in culture (class I lines). However, this capacity is seen in few hESC isolates. Many hESC lines have already undergone XCI (class II and III). Unexpectedly, there is a tendency to lose XIST RNA expression during culture (class III). Despite losing H3-K27 trimethylation, the inactive X of class III lines remains transcriptionally suppressed, as indicated by Cot-1 RNA exclusion. We conclude that hESC lines are subject to dynamic epigenetic reprogramming ex vivo. Given that XCI and cell differentiation are tightly linked, we consider implications for hESC pluripotency and differentiation potential.